EKSPERIMENTASI STRATEGI PEMBELAJARAN LIGTENING THE LEARNING CLIMATE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI KECERDASAN EMOSIONAL - Ratna Anngraeni, Dian (STKIP YPM Bangko, 2019)
This study aims to describe mathematical communication skills in terms of emotional intelligence using Ligtening The Learning Climate learning strategies better than conventional learning. The research method used is the experimental method with a quantitative approach using a 2 x 3 factorial design with a population of class VIII students totaling 4 classes. The sampling technique uses Simple Random Sampling, selected class VIII C as the experimental class and class VIII B as the control class, and both classes are grouped based on their emotional intelligence. Data collection uses test techniques for mathematical communication ability variables and questionnaires for emotional intelligence. The results of data analysis showed that hypotheses 1, 3 and 4 obtained tcount > ttable, hypothesis 2 obtained tcount <ttable and hypothesis 5 obtained Fcount > Ftable, it can be concluded: overall student mathematical communication skills with moderate and low emotional intelligence using the Learning The Learning Climate learning strategy is better than conventional learning. Mathematical communication skills of students who have high emotional intelligence use Ligtening The Learning Climate learning strategy is not better or equal to conventional learning. There is an interaction between emotional intelligence and learning strategies in influencing mathematical communication skills.